2008
DOI: 10.1063/1.2974098
|View full text |Cite
|
Sign up to set email alerts
|

Why are ionic liquid ions mainly associated in water? A Car–Parrinello study of 1-ethyl-3-methyl-imidazolium chloride water mixture

Abstract: In this study we present the results of a first principles molecular dynamics simulation of a single 1-ethyl-3-methyl-imidazolium chloride [C(2)C(1)im][Cl] ion pair dissolved in 60 water molecules. We observe a preference of the in plane chloride coordination with respect to the cation ring plane as compared to the energetic slightly more demanding on top coordination. Evaluation of the different radial distribution functions demonstrates that the structure of the hydration shell around the ion pair differs si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
145
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(159 citation statements)
references
References 62 publications
12
145
0
1
Order By: Relevance
“…Furthermore, it was reported that IL cations can exhibit a depolarization effect on water molecules. Thus, the dipole moment of water decreases with increasing IL concentration in several aprotic and protic ILs [122][123][124] , which can be counteracted in presence of strong hydrogen bond acceptor anions. Another interesting effect is also the formation of carbenes in presence of water 122 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that IL cations can exhibit a depolarization effect on water molecules. Thus, the dipole moment of water decreases with increasing IL concentration in several aprotic and protic ILs [122][123][124] , which can be counteracted in presence of strong hydrogen bond acceptor anions. Another interesting effect is also the formation of carbenes in presence of water 122 .…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the evaluation of L(c) also requires assumptions, see Section 3.1. It must also be remembered that the DRS experiments require rather high concentrations so that extrapolation of K A (I) with eqn (16) 15 and the excellent agreement between the rotational correlation time calculated for the CIP and the experimental value, SIP formation also seems unlikely in water.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
“…As an alternative, the CIP dipole moments obtained from semiempirical MOPAC 50 calculations with solvent-effect corrections 77 were adopted. Since these calculations indicated the existence of various conformers of similar energy, their dipole moments were averaged, yielding the values listed in 15 These dipole moments were used to calculate ion-pair concentrations c IP (Fig. 8(a)) and K A values (Fig.…”
Section: Dielectric Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations